Case Study: Removal of Calculi in The Bladder using Cystotomy Method in Female Pomeranian Mix Pekingese Dog at Winadi Vet Animal Clinic Malang - Fenti Nursafitri; Dian Vidiastuti; Winda Syafitri (Veterinary Biomedical and Clinical Journal, 2022)
Urolithiasis is a disease caused by calculi, crystals, or excessive sediment in the urinary tract, which is generally composed of one or more types of minerals such as struvite, calcium oxalate, calcium phosphate, uric acid, and cystine. A 10-year-old female Pomeranian mix Pekingese dog was referred to Winadi Vet Animal Clinic Malang with clinical signs of dysuria, strangury, and hematuria. The physical examination findings were lethargy, caudal abdominal pain, and bladder distension. Radiological examination results indicated distension in the urinary bladder containing two stones occupying with clear margins and radiopaque-like opacity, with lengths of 3.44 cm and 3.35 cm, respectively. Cystotomy to remove the calculi was performed by incision on the midline.The urinary bladder was closed using a two-layer closure suture type, the first layer used simple interrupted, and the second layer used simple continuous suture with 3-0 polyglactin (Vicryl®) suture. The animal recovered on the fourteenth day after surgery